A single dose of SARS-CoV-2 FINLAY-FR-1A vaccine enhances neutralization response in COVID-19 convalescents, with a very good safety profile: An open-label phase 1 clinical trial - Arturo Chang-Monteagudo; Rolando Ochoa-Azze; Yanet Climent-Ruiz; Consuelo Macías-Abraham; Laura Rodríguez-Noda; Carmen Valenzuela-Silva; Belinda Sánchez-Ramírez; Rocmira Perez-Nicado; Tays Hernández-García; Ivette Orosa-Vázquez; Marianniz Díaz-Hernández; María de los Ángeles García-García; et al. (Elsevier, 2021)
Background: As a first step towards a vaccine protecting COVID-19 convalescents from reinfection, we evaluated FINLAY-FR-1A vaccine in a clinical trial. Methods: Thirty COVID-19 convalescents aged 22-57 years were studied: convalescents of mild COVID-19, asymptomatic convalescents, both with PCR-positive at the moment of diagnosis; and individuals with subclinical infection detected by viral-specific IgG. They received a single intramuscular injection of the FINLAY-FR-1A vaccine (50 µg of the recombinant dimeric receptor binding domain). The primary outcomes were safety and reactogenicity, assessed over 28 days after vaccination. The secondary outcome was vaccine immunogenicity. Humoral response at baseline and following vaccination was evaluated by ELISA and live-virus neutralization test. The effector T cellular response was also assessed. Cuban Public Registry of Clinical Trials, WHO-ICTRP: https://rpcec.sld.cu/en/trials/RPCEC00000349-En. Findings: No serious adverse events were reported. Minor adverse events were found, the most common, local pain: 3 (10%) and redness: 2 (6·7%). The vaccine elicited a >21 fold increase in IgG anti-RBD antibodies 28 days after vaccination. The median of inhibitory antibody titres (94·0%) was three times greater than that of the COVID-19 convalescent panel. Virus neutralization titres higher than 1:160 were found in 24 (80%) participants. There was also an increase in RBD-specific T cells producing IFN-γ and TNF-α. Interpretation: A single dose of the FINLAY-FR-1A vaccine against SARS-CoV-2 was an efficient booster of pre-existing natural immunity, with excellent safety profile. Funding: Partial funding for this study was received from the Project-2020-20, Fondo de Ciencia e Innovación (FONCI), Ministry of Science, Technology and the Environment, Cuba.